Proxidant*antioxidant balance in supplemented elite female volleyball athletes during a six week training period - Martinovic, J.; Dopsaj, V.; Kotur-Stevuljevic, J.; Dopsaj, M.; Vujovic, A.; Stefanovic, A.; Nesic, G. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: The objectives of this study were: 1) to evaluate pro-oxidant-antioxidant balance (PAB) associations with the commonly measured parameters of oxidative stress and antioxidatve defence in elite female volleyball athletes; 2) to investigate changes in the parameters of oxidative stress during a period of intense training and dietary antioxidant supplementation. METHODS: Twenty-seven female volleyball players participated in this study. Blood samples were collected the day before the pre-competitive mesocycle training period began. After the first blood sample donation and during the next six weeks fourteen players (supplemented group) received a cocktail of antioxidants while thirteen of them (control group) received no dietary supplementation. The following parameters were measured: reactive oxygen metabolites (ROMs), superoxide anion (O2-), malondialdehyde (MDA), advanced oxidation protein products (AOPP), lipid hydroperoxides (LOOH), biological antioxidative potential (BAP), paraoxonase activity toward paraoxon (POase) and diazoxon (DZOase), superoxide dismutase (SOD), total sulphydryl group concentration (SH groups) and pro-oxidant-antioxidant balance. RESULTS: Significant associations were observed between biomarkers of oxidative damage with PAB in multiple linear regression model in the supplemented and the control groups (82.3% vs. 83.1%) before training and in the control group (82.1%) after training. Significant associations between antioxidative defence parameters and PAB values were found in the supplemented group after six-weeks of training (57%). CONCLUSION: In the absence of antioxidant supplementation, PAB values were dependent on the association with biomarkers of oxidative damage before and after training. After a six-week training period and the applied antioxidant supplementation, PAB values were under the influence of non-enzymatic anti-oxidative defence.